A comparison of augmented feedback and didactic training approaches to reduce spine motion during occupational lifting tasks. (February 2022) - Chan, Victor C.H.; Welsh, Timothy N.; Tremblay, Luc; Frost, David M.; Beach, Tyson A.C.
Abstract: Manual handling training may be improved if it relied on the provision of individualized, augmented feedback about key movement features. The purpose of this study was to compare the reduction in sagittal spine motion during manual lifting tasks following two training approaches: didactic (DID) and augmented feedback (AUG). Untrained participants ( n = 26) completed lifting tests (box, medication bag, and paramedic backboard) and a randomly-assigned intervention involving 50 practice box lifts. Lifting tests were performed immediately before and after training, and one-week after interventions. Both groups exhibited reductions in spine motions immediately and one-week after the interventions. However, the AUG intervention group elicited significantly greater reductions in 5 of 12 between-group comparisons (3 tasks × 4 spine motion variables). The results of the current study support the use of augmented feedback-based approaches to manual handling training over education-based approaches. Highlights: Two manual lifting training approaches were compared. A didactic intervention (DID) was used to deliver lifting-related education. An augmented feedback intervention (AUG) provided cues about key movement features. DID and AUG elicited significant reductions in spine motion at both time points. AUG elicited greater reductions compared to DID in 5 of 12 variables analyzed.